Fishing in deep waters: The development of a deep-sea fishing coastal fleet in Norway. (January 2016) - Standal, Dag; Sønvisen, Signe Annie; Asche, Frank
Abstract: In the post-war political landscape in Norway, it has been a rooted consensus to maintain the coastal fleet as the largest and most important segment of the Norwegian fishing fleet. The simple and open technology, and low entrance costs in the coastal fisheries have secured employment in fisheries dependent districts, especially in Northern Norway. In order to protect the coastal fleet from the deep-sea fleet, the regime fixed the resource allocation and secured the coastal vessels with the largest share of the national TAC for cod. However, despite the strong institutionalization of the coastal fleet, the regime has not managed to avoid a rapid growth of deep-sea vessels and reallocation of quotas within the coastal group. Highlights: The individual vessel quota regime (IVQ) has not managed to secure a stable fleet structure within the coastal fleet segment. The transformation of coastal vessels into deep-sea vessels represents a redistribution of quota rights among fixed groups. Shifts in the resource base and differences in efficiency among coastal vessels is complex to handle for a nontransferable quota regime (IVQ). Significant changes in the coastal fleet structures put pressure to the legitimacy of the resource allocation regime.